De Garengeot's hernia: a comprehensive review. - Kalles, V; Mekras, A; Mekras, D; Papapanagiotou, I; Al-Harethee, W; Sotiropoulos, G.; Liakou, P.; Kastania, A; Piperos, T; Mariolis-Sapsakos, T (Hernia, 2013)
PURPOSE: Acute appendicitis within a femoral hernia is a rare condition that was first described by Rene Jacques de Garengeot. In the present study, we summarize the existing evidence on de Garengeot's hernia, with special emphasis on its clinical presentation and diagnostic approach. METHODS: A thorough search of the English-language literature published between 1980 and 2011 was performed. Studies reporting cases of de Garengeot's hernia were selected using specific inclusion criteria (description of femoral hernia appendicitis, statement of patient demographics and symptoms, and statement of diagnostic tests performed). RESULTS: Thirty-one studies that encompassed 36 patients (28 women, mean age 71.5 years) with de Garengeot's hernia were included in our analysis. Patients presented with a right groin mass in 35 (97 %) cases. The mass was almost always painful (n = 35, 97 %), while 14 (39 %) of the patients were febrile. Mean duration of symptoms was 5.17 days. Fifty-six percent of the groin masses were erythematous. Leukocytosis was present in 67 % of the patients, and 25 patients underwent imaging investigation with X-ray (n = 11), Ultrasound (n = 5) or Computed Tomography (CT, n = 9). Twenty percent of the Ultrasound and 44 % of the CT studies were diagnostic, leading to an overall rate of 14 % of femoral hernia appendicitis preoperative diagnosis. Eighty-one percent of the patients underwent herniorrhaphy with sutures while a mesh was used in 19 %. Mean hospital stay was 6.23 days. CONCLUSION: Preoperative diagnosis of de Garengeot's hernia is difficult due to its atypical clinical presentation. Further surgical treatment depends on the surgeon's sound clinical judgment.
Keywords: Aged; Appendicitis; Female; Hernia, Femoral; Humans; Male; Tomography, X-Ray Computed